UNNAMED GRAVES: THE DEATH OF WORKERS IN THE MATARAM DITCH CONSTRUCTION DURING THE JAPANESE OCCUPATION ERA: Array - 1 (Jurnal Kearsipan, 2021)
This study discusses the death of workers in the Mataram ditch construction during the Japanese occupation era as represented by 6 graves in Barongan Hamlet, Banyurejo Village, Kapanewon Tempel, Sleman Regency, Yogyakarta Province. A sad story that is not recorded in the history of Yogyakarta or the history of sewer construction, but becomes part of the collective memory of the community. Early research on the Mataram ditch, which mostly focused on the palace and Sultan Hamengkubuwono IX as the center of the story, eliminates this kind of story. Inevitably, the construction of sewers has been narrated without problems and has succeeded in boosting the welfare of farmers. The story outside of this big narrative will be offered from this research.